Novel insights into mechanisms for Pak1-mediated regulation of cardiac Ca2+ homeostasis - Wang, Yanwen; Tsui, Hoyee; Bolton, Emma L.; Wang, Xin; Huang, Christopher L.-H.; Solaro, R. John; Ke, Yunbo; Lei, Ming (Frontiers in Physiology, 2015)
A series of recent studies report novel roles for Pak1, a key member of the highly conserved family of serine-threonine protein kinases regulated by Ras-related small G-proteins, Cdc42/Rac1, in cardiac physiology and cardioprotection. Previous studies had identified Pak1 in the regulation of hypertrophic remodeling that could potentially lead to heart failure. This article provides a review of more recent findings on the roles of Pak1 in cardiac Ca2+ homeostasis. These findings identified crucial roles for Pak1 in cardiomyocyte Ca2+ handling and demonstrated that it functions through unique mechanisms involving regulation of the post-transcriptional activity of key Ca2+-handling proteins, including the expression of Ca2+-ATPase SERCA2a, along with the speculative possibility of an involvement in the maintenance of transverse (T)-tubular structure. They highlight important regulatory functions of Pak1 in Ca2+ homeostasis in cardiac cells, and identify novel potential therapeutic strategies directed at manipulation of Pak1 signaling for the management of cardiac disease, particularly heart failure.